Análisis, diseño y desarrollo de una aplicación móvil para la visualización del consumo de energía eléctrica residencial utilizando las plataformas Android y Raspberry Pi - Licto Sánchez, Carlos Eduardo (2016)
Present Development Project implemented prototype of the United Nations display Electric Energy Consumption in Households of Quito. The mayor goal of this project is to allow family boos to control Electric Energy Consumption and of course its economy. The Project has to be an economical solution; for that reason, it was development using free platforms. Prototype has two main components: The first part is Server Technology developed on the Raspberry Pi, which is working on Archlinux operating system. Server takes measurement data Sent from the electrical meter by serial communication and stores them in a database, which is managed by two scripts coded in Python and Ruby. Finally that data is published in Web services for later consumption. The Second Part of the Solution is an application developed in Java for devices with Android. This application consumes the web services data and filters it. The data is handled to perform consumption graphs.